1966
DOI: 10.1128/jb.92.5.1383-1387.1966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Chloride and pH on Enterotoxin B Production

Abstract: The growth and production of enterotoxin B by Staphylococcus aureus strain S-6 in Brain Heart Infusion broth with 2 to 16% sodium chloride and an initial pH of 5.1 to 6.9 was studied during a 10-day incubation period at 37 C. Growth was good atpH 6.9 and with a 16% concentration of salt, but no cells survived after 10 days of incubation at pH 5.1 and with a 16% concentration of salt. With geldiffusion technique, enterotoxin B was detected in broth with pH 6.9 and up to 10% salt or pH 5.1 and up to 4% salt. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

1969
1969
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 7 publications
4
36
0
1
Order By: Relevance
“…As shown ( Table 7) the NaC1-pH combinations needed for inhibition were different between C. botulinum types, with lower concentrations of NaCl being required for type E than for types A and B at similar pH values. Acidity and NaCl interaction against growth of C. botulinum and other organisms have also been reported by several other researchers (Baird-Parker and Freame 1967;Genigeorgis and Sadler 1966;Ingram 1962;Baird-Parker and Baillie 1973;Roberts and Ingram 1973). Recent results by Hauschild and Hilsheimer (1979) indicated that in bottled lumpfish caviar prepared with different NaCl concentrations, inoculated with C. (1972) botulinum spores and stored at 30°C, growth and toxin production were inhibited by combinations of > 3.95% (w/v) NaCl and pH < 5.2 and of > 4.67% (w/v) NaCl and pH < 5.6.…”
Section: Acidity (Ph)supporting
confidence: 70%
“…As shown ( Table 7) the NaC1-pH combinations needed for inhibition were different between C. botulinum types, with lower concentrations of NaCl being required for type E than for types A and B at similar pH values. Acidity and NaCl interaction against growth of C. botulinum and other organisms have also been reported by several other researchers (Baird-Parker and Freame 1967;Genigeorgis and Sadler 1966;Ingram 1962;Baird-Parker and Baillie 1973;Roberts and Ingram 1973). Recent results by Hauschild and Hilsheimer (1979) indicated that in bottled lumpfish caviar prepared with different NaCl concentrations, inoculated with C. (1972) botulinum spores and stored at 30°C, growth and toxin production were inhibited by combinations of > 3.95% (w/v) NaCl and pH < 5.2 and of > 4.67% (w/v) NaCl and pH < 5.6.…”
Section: Acidity (Ph)supporting
confidence: 70%
“…in cured meats with NaCl in the brine up to 9.2% (-C 0.92%), a value 2 to 5 times greater than that found in commercially prepared cured meats. The value is comparable to the 10% salt found to be the highest content permitting enterotoxin-B production in 16 days of aerobic incubation in brain heart infusion broth of pH 6.9 (Genigeorgis et al, 1966a). Thus, manipulation of salt content within the levels acceptable to consumer taste will not control staphylococcal enterotoxin production, as can be done for Clostwidium botulinurn type E (Foster et al, 1966).…”
Section: Enterotoxin Production In Laboratory-cured Hamsmentioning
confidence: 63%
“…Experimental enterotoxin production in ham has been studied by Kelly et al (1936) Thatcher et al (1962) and Casman et al (1963). Enterotoxin B production in brain heart infusion broth as affected by sodium chloride and pH has recently been studied in our laboratory (Genigeorgis et al, 1966a). The present paper describes a preliminary attempt to induce experimental enterotoxin-B production in a variety of hams under selected environmental conditions.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Numerous publications investigated the production of enterotoxins under stress conditions using immunological methods (Genigeorgis & Sadler, 1966;McLean et al, 1968;Troller, 1971;Domenech et al, 1992). However, these data are of limited value, as it was later shown that loss of serological recognition does not equal loss of biological/emetic activity (Bennett, 2005).…”
Section: Introductionmentioning
confidence: 99%